Communication: The shifts in messaging … and their meaning. Issue 1 (20th April 2023) - Skipworth, Stan
Abstract : Recently, my wife and I were enjoying a mid‐morning walk while vacationing on the island of Kauai when we began to take note of a variety of news and current events. As we continued our conversation along the beach, we more fully recognized several changes that have taken shape over the last several years in the scope of communication — and communications .